What is meaning?: studies in the development of significance - Welby, Victoria (Foundations of semiotics, 1983)
In "What is Meaning" (1903) the author elaborates on the fundamental tenets of her theory of sign, to which she gave the overall term ‘significs’. One of the main obstacles to an adequate theory of meaning, in Lady Welby’s opinion, is the unfounded assumption of fixed sign meaning. "There is, strictly speaking, no such thing as the Sense of a word, but only the sense in which it is used – the circumstances, state of mind, reference, ‘universe of discourse’ belonging to it. The Meaning of a word is the intent which it is desired to convey – the intention of the user. The Significance is always manifold, and intensifies its sense as well as its meaning, by expressing its importance, its appeal to us, its moment for us, its emotional force, its ideal value, its moral aspect, its universal or at least social range." This facsimile of the 1903 edition of "What is Meaning" is accompanied by an essay on "Significs as a Fundamental Science" by Achim Eschbach, and "A Concise History of Significs" by G. Mannoury.